Comparable membrane permeability can be achieved in granular and flocculent anaerobic membrane bioreactor for sewage treatment through better sludge blanket control. (April 2019) - Wang, K.M.; Soares, A.; Jefferson, B.; McAdam, E.J.
Highlights: UASB configured AnMBRs are viable for municipal wastewater treatment. At 20 °C, membrane permeability of granular and flocculent AnMBR is comparable. At 10 °C, flocculent UASB solids breakthrough increases membrane fouling. Pseudo dead-end gas sparging achieves energy neutral sewage treatment for both MBR. Solids management strategy ensures flocculent AnMBR comparable to granular. Abstract: In this study, granular and flocculent sludge are compared as seeding options for UASB configured anaerobic MBR, to establish the impact of biomass selection on sustaining membrane permeability for sewage treatment. When operated as an UASB (10 °C), similarly poor organics removal was observed for both inocula, which was overcome by membrane integration, producing solids-free permeate and consistently low CODt (34–39 mg L −1 ) and BOD5 (10–13 mg L −1 ), sufficient to meet discharge standards. At an average sewage temperature of 22 °C, membrane permeabilities in granular (G-AnMBR) and flocculent (F-AnMBR) systems were comparable. However, at lower temperature (10 °C), significant fouling was observed in F-AnMBR at a flux of 7.5 L m −2  h −1 . The permeability decline was ascribed to a decreased particle settling velocity which induced washout of smaller particles into the membrane tank, subsequently increasing the colloidal concentration due to the floc erosion induced by gas sparging. This was confirmed by halving UASB upflow velocity in the F-AnMBR, which reduced pCOD and colloidal load by 31–36% onto the membrane, permitting comparable permeability to G-AnMBR. The UASB configured AnMBR promoted low solids loading onto the membrane, enabling pseudo dead-end gas sparging to be used which reduced specific energy demand. Analysis of the dead-end filtration cycle attributed the primary resistance (85–88%) to the development of a concentrated but less compact cake. Importantly, this study evidences comparable permeabilities in G-AnMBR and F-AnMBR through controlling solids retention, and specifying filtration cycle length to minimise solids deposition, such that low energy membrane operation can be achieved (<0.122 kW h m −3 ).